The sports rehabilitation therapists' guidebook : accessing evidence-based practice - Papadopoulos, Konstantinos (Physiotherapist) (New York, NY : Routledge, 2020)
"The Sports Rehabilitation Therapists' Guidebook is a well-equipped, comprehensive, practical, evidence-based guide that seeks to assist both students and graduate sport practitioners. The book is designed to be a quick-reference book during assessment and treatment planning giving instant access to figures and case scenarios. It introduces evidence-based practice in all principal areas of sport rehabilitation such as anatomy, musculoskeletal assessment, pitch-side care, injury treatment modalities and exercise rehabilitation principles and related areas and is designed to be more flexible than usual single focus books. Written by a team of expert contributors offering a systematic perspective on core concepts. It can be used as a guide in each stage of the sport rehabilitation process and it is an asset for sport clinical practitioners such as sport rehabbers, sport therapists, personal trainers, strength and conditioning coaches as well as for students on these and related courses in their daily practice on core clinical placements such as a clinic/sporting environment, pitch side and university"--
Includes bibliographical references and index.
Keywords: Sports injuries -- Patients -- Rehabilitation; Sports injuries -- Treatment